Performance evaluation of the new Dymind automated hematology analyzer - Penglong, Tipparat; Tepakhan, Wanicha; Tehyoh, Nasra; Songkhla, Yanisa Na; Songnak, Chakkrit; Srinoun, Kanitta (Practical laboratory medicine, 2025)
The Dymind automated hematology analyzer includes the five-part analyzers DF55 and DH76 and the six-part analyzer DH615, which features reticulocyte parameters and an artificial intelligence-driven analysis technology. This study evaluated the performance of these analyzers in assessing precision and conducting method comparisons to determine the diagnostic accuracy and clinical efficacy of the Dymind automated system. We assessed precision and conducted a method comparison by analyzing complete blood count (CBC) and white blood cell (WBC) differential data from the Dymind DF55, DH76, and DH615. Results were compared with those from the Sysmex XN-3000 analyzer. The Dymind-series analyzers demonstrated high between-run precision for all CBC and WBC differential parameters. Method comparison revealed a strong correlation (r = 0.80–0.99) between the Dymind and Sysmex analyzers for most CBC parameters, except for mean corpuscular hemoglobin concentration and basophil counts. The Dymind-series analyzer exhibited a strong analytical performance across all standard CBC and WBC differential count parameters, validating their precision and comparability with a reference system for routine hematological testing. [Display omitted] •Evaluated the performance of Dymind automated hematology analyzers (DF55, DH76, and DH615).•Demonstrated high between-run precision for CBC and WBC differential parameters.•Strong correlation (r = 0.80–0.99) with the Sysmex XN-3000 analyzer across most parameters.•Validates Dymind analyzers for reliable routine hematological testing.